1968
DOI: 10.1063/1.1669812
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Properties of Hexafluoroacetone. II. Fluorescence Quenching by Oxygen, Nitric Oxide, and Unsaturated Hydrocarbons

Abstract: It has been observed that oxygen, nitric oxide, olefins, and benzene quench the fluorescence of hexafluoroacetone. Fluorescence lifetime measurements were used to evaluate rate constants for quenching. Quenching efficiencies were found to follow the order piperylene> isobutylene > propylene > benzene> ethylene > oxygen. Olefin quenching efficiencies decreased with increasing temperature. These results suggest a mechanism involving an unstable intermediate, perhaps a complex with some charge-transfer character,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Nevertheless, CT interactions with oxygen must be important not only for aromatic ketones but also for triplet-excited aliphatic ketones. For example, the quenching rate constant for triplet hexafluoroacetone, for which CT contributions are expected to be extremely unfavorable, has been determined as 0.45 × 10 8 M -1 s -1 in the gas phase, i.e., 1 order of magnitude lower than for acetone. Table provides a survey of the energetic criteria that may govern oxygen quenching of different types of n,π* sensitizers, namely, ketones and azoalkanes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, CT interactions with oxygen must be important not only for aromatic ketones but also for triplet-excited aliphatic ketones. For example, the quenching rate constant for triplet hexafluoroacetone, for which CT contributions are expected to be extremely unfavorable, has been determined as 0.45 × 10 8 M -1 s -1 in the gas phase, i.e., 1 order of magnitude lower than for acetone. Table provides a survey of the energetic criteria that may govern oxygen quenching of different types of n,π* sensitizers, namely, ketones and azoalkanes.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen - Quenching Rate Constants of Singlet States . The absence of fluorescence quenching of aliphatic ketones by oxygen has been a standing problem, since it was long unclear whether it is due to true inefficiency or simply short singlet lifetimes. , The situation was remedied by the observation that the extraordinary long-lived (relative to other ketones) singlet state of hexafluoroacetone in the gas phase ( 1 τ = 84 ns) 22 is quenched by oxygen with a rate constant of 7.6 × 10 7 M -1 s -1 , which implied that oxygen quenching with reduced efficiency may occur for other aliphatic ketones as well. Indeed, fluorescence quenching by oxygen was found to be quite inefficient for the examined aliphatic ketones ( k q ≈ 2 × 10 9 M -1 s -1 ; see Table ) but is nonetheless significant, in particular in oxygen-saturated solvents with high oxygen solubilities.…”
Section: Discussionmentioning
confidence: 99%
“…Very little has been published on O 2 quenching of S 1 (nπ*) states. Ware reported the very small value of = 7.6 × 10 7 M -1 s -1 for hexafluoroacetone in the gas phase . Measurements made by Scaiano and Nau in nonpolar solvents yielded = (1.7−2.7) × 10 9 M -1 s -1 for several S 1 (nπ*)-excited alkanones 413 and = 8 × 10 9 M -1 s -1 for two S 1 (nπ*)-excited azoalkanes .…”
Section: Rate Constants Of S1-state Quenchingmentioning
confidence: 97%
“…Kinetic studies on the deactivation of excited singlet (S 1 ) and triplet (T 1 ) states by O 2 have been performed since the early 1950s. These investigations made it clear that O 2 quenches excited states of both multiplicities, with variable rate constants close to the diffusion-controlled limit. Later studies showed that both quenching processes can lead to energy transfer, which means that the overall quantum yield of singlet oxygen formation, Q Δ , may vary between 0 and 2.…”
Section: Photosensitized Production Of Singlet Oxygenmentioning
confidence: 99%
“…Although the ideal condition for the calibration measurements would be a case of having exactly the same charge composition as the engine measurements, but previous studies indicated that the ketones' fluorescence at atmospheric pressure is relatively insensitive to the bath gas composition and quenching due to the dominant non-collision dependent decay rates of the first excited singlet state [45,46]. In addition, experimental test results at elevated pressures up to 20 bar, indicated that 3-pentanone shows even less sensitivity to oxygen-related quenching influences than does other ketones [47] which was associated with the electron density at the carbonyl group [48]. In addition, it should be noted that although the temperature calibration measurements did not cover the full range of incylinder charge temperature values for spark ignition engine operation, but it was sufficient for global charge temperature measurements during the compression stroke and up to ignition timing as well as local end-gas temperature measurements during the combustion.…”
Section: Temperature Calibration Measurementsmentioning
confidence: 91%